2020
DOI: 10.1186/s12711-020-00553-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of European autochthonous and commercial pig breeds allows the detection of signatures of selection for adaptation of genetic resources to different breeding and production systems

Abstract: Background: Natural and artificial directional selection in cosmopolitan and autochthonous pig breeds and wild boars have shaped their genomes and resulted in a reservoir of animal genetic diversity. Signatures of selection are the result of these selection events that have contributed to the adaptation of breeds to different environments and production systems. In this study, we analysed the genome variability of 19 European autochthonous pig breeds (Alentejana,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 104 publications
6
68
0
Order By: Relevance
“…Collected DNA or samples from previous projects were also re-used in this study. This work took advantage from a study design developed within the Horizon 2020 TREASURE project [65][66][67][68] . Animals included in the study were 30 or 35 from each of the 22 pig breeds that were investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collected DNA or samples from previous projects were also re-used in this study. This work took advantage from a study design developed within the Horizon 2020 TREASURE project [65][66][67][68] . Animals included in the study were 30 or 35 from each of the 22 pig breeds that were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of variability included a total of 22 European pig breeds and wild boars and two Asian pig populations using next generation sequencing data (NGS). This dataset covered a broad number of pig genetic resources raised in Europe 65,66 in comparison with a few Asian populations. The obtained results could be useful (i) to establish a risk evaluation system in a "One Health" approach, including information on the diversity of pig populations, (ii) to define cross species evolutionary analyses of genes involved in coronavirus infections and (iii) to identify natural genetic variability within the Sus scrofa species that could help to design genetic improvement strategies to increase genetic resistance in commercial and autochthonous pig populations against emerging and re-emerging coronavirus diseases.…”
mentioning
confidence: 99%
“…2019) and whole genome resequencing data (Bovo et al . 2020a,b). Genome‐wide data indicated that the average persistence and strength of LD between markers and SNP‐based effective population size varied among breeds depending on the genetic structures and history of these breeds that had experienced different genetic events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…DNA markers in the MC1R gene have been already proposed to authenticate pork from domestic pig breeds or wild boars [ 12 , 18 , 19 ]. Additional genes affecting coat colour have been described in pigs and some of them might contribute to determine the classical colour observed in the Mora Romagnola pigs [ 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%